2017
DOI: 10.1111/1462-2920.13643
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural soil denitrifiers possess extensive nitrite reductase gene diversity

Abstract: Denitrification transforms nitrogen applied as fertilizer and emits N O, which is a potent greenhouse gas. Very little is known about the identities of abundant and active denitrifiers in agricultural soils. We coupled DNA stable-isotope probing (DNA-SIP) with flow-through reactors (FTRs) to detect active agricultural soil denitrifiers. The FTRs were incubated with nitrate and C -glucose under anoxic conditions and sampled at multiple time points. Labelled DNA from active microorganisms was analyzed by 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 99 publications
3
34
2
Order By: Relevance
“…nirK and nirS. This limited coverage has been noted previously (Bonilla-Rosso et al, 2016;Decleyre et al, 2016;Coyotzi et al, 2017). Consistently, 361 nirK nucleotide sequences of Bacteria and Archaea in this study were aligned and clustered into two major clades (Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…nirK and nirS. This limited coverage has been noted previously (Bonilla-Rosso et al, 2016;Decleyre et al, 2016;Coyotzi et al, 2017). Consistently, 361 nirK nucleotide sequences of Bacteria and Archaea in this study were aligned and clustered into two major clades (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Although some of the existing primers were designed for universal nirK amplification Hallin and Lindgren, 1999;Casciotti and Ward, 2001;Rösch et al, 2002;Chénier et al, 2003;Liu et al, 2003;Henry et al, 2004;Chen et al, 2010), in silico primer tests against the nirK nucleotide sequences indicated that they covered 0.28%-27.4% of the overall nirK sequences (data not shown); they actually only cover clade I (Table 1). This limited coverage has been noted previously (Bonilla-Rosso et al, 2016;Decleyre et al, 2016;Coyotzi et al, 2017). Among all the primers targeting clade I of nirK, nirKC1F/nirKC1R by Wei and colleagues (2015b) had the highest coverage (89.3%, Table 1).…”
Section: Resultsmentioning
confidence: 50%
“…All these products may be released during denitrification. Reactions are regulated by the enzymes nitrate reductase and nitrite reductase ( Figure 9; Coyotzi et al, 2017). The reactions are carried out by denitrifying bacteria that are widely distributed across the bacterial taxa.…”
Section: Biological Denitrificationmentioning
confidence: 99%
“…Targeted amplicon sequencing of 13 C-enriched DNA provides phylogenetic information about populations of interest ( Neufeld et al, 2007 ). When combined with functional information, DNA-SIP informs the understanding of resource availability and allocation in complex environments ( Li et al, 2011 ; Coyotzi et al, 2017 ). Isothermal calorimetry combined with 13 C-SIP has the potential to provide valuable insight into the simultaneous identity of active members and physiology of the microbial communities, enabling greater understanding of the role community composition plays in soil C dynamics.…”
Section: Introductionmentioning
confidence: 99%